Guia para prevenção de lesão por pressão em idosos - Farias, Ana Patricia do Egito Cavalcanti de (2021)
Introduction: In the natural aging process, the elderly may have physical or cognitive limitations that lead to a certain dependence. In addition, they can develop chronic diseases that require constant attention and the need to stay in hospital. One of the aggravating factors of the long stay is the possibility of developing pressure injuries. In order to prevent and treat, a multidisciplinary team prepared, together with the family caregiver, is of utmost importance to assist in the necessary care. Objectives: To analyze the scientific production about the prevention of pressure injuries in the elderly, identifying the predisposing factors for its appearance; Understand the perception of family caregivers about prevention of pressure injuries in the elderly and Build an educational guide for the prevention of pressure injuries in the elderly. Method: This is a methodological study, structured in three stages: in the first one, an attempt was made to identify scientific evidence from an integrative review with the search for scientific articles in the month of September 2019 in the LILACS, MEDLINE, CINAHL, Scopus and Web of Science databases. In the second stage, an exploratory, descriptive research was carried out with a qualitative approach on the perception of family caregivers in the prevention of pressure injuries in the elderly, with the sample consisting of 50 family caregivers of elderly patients who were hospitalized in the medical clinic sector of the Hospital University student Lauro Wanderley, from October 2020 to February 2021. They responded to a semi-structured interview whose transcribed data were organized using the software IRAMUTEQ. In the third stage, a guide for the prevention of pressure injuries in the elderly was developed with guidance for family members. Results and Discussion: In the first stage, 15 articles were selected from a universe of 618 publications. The analysis made it possible to identify that advanced age, presence of comorbidities, malnutrition, immobility, and prolonged hospital stay are configured as risk factors. In the second stage, the content from the textual corpus was analyzed and organized into classes, observing the representativeness: Class 1- “Understanding the cause of LPP”; Class 2- “Difficulties in the care of the LPP”; Class 3- “Experiences acquired with LPP”; “Class 4- “Care for LPP”; Class 5- "Guidelines received in the management of LPP". For the construction of the guide, the results of the qualitative study with family caregivers was used as a basis. Final Considerations: The results of this research allowed the identification of several gaps in caregivers in their daily lives regarding care with the elderly. It is expected that the guide can contribute to learning, serving as a facilitator, promoting the necessary knowledge in the care provided by caregivers, encouraging behavior change and reinforcing prevention, improving the quality and life of the elderly.